Analisis Pengaruh Konfigurasi Branch Line System terhadap Kerugian Kehilangan Tekanan di Tee Junction - Ali, Muhammad; Nugroho , Setyo ; Ulum , Achmad Bahrul (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Piping network is one of the needs as a means of distributing water or other fluids in everyday life and industry. Water is used to produce steam in Power Plant to generate electricity. Selection of the right size, material and installation can help to reduce initial costs, maintenance costs and as a safety factor. Pipe bifurcation is a piping component needed in the installation so that the fluid can be split to several destinations. One of bifurcation of pipe is tee-junction. This study discusses the distribution of pressure at tee junction with experiments through measurements in the Branch Line System test module and numerical methods using the Computational Fluid Dynamics simulation of ANSYS. This research was conducted by varying the configuration of several branching using a constant mass flow entering the tee junction. The results obtained show that the pressure value at the tee junction inlet decreases at outlets 90? and 180? due to pressure loss. The highest loss of pressure is 5884 Pa in the branch flow and 4903 Pa in the line flow while the smallest loss is 2942 Pa for branch flow and 1961 Pa for line flow. Separation and recirculation flow is occured in the junction at the junction.